Tuning Bulk O2 and Nonbonding Oxygen State for Reversible Anionic Redox Chemistry in P2‐Layered Cathodes. (23rd February 2022) - Li, Zhenrui; Kong, Weijin; Yu, Yang; Zhang, Jicheng; Wong, Deniz; Xu, Zijian; Chen, Zhenhua; Schulz, Christian; Bartkowiak, Maciej; Liu, Xiangfeng
Abstract: Improving the reversibility of oxygen redox is quite significant for layered oxides cathodes in sodium‐ion batteries. Herein, we for the first time simultaneously tune bulk O2 and nonbonding oxygen state for reversible oxygen redox chemistry in P2‐Na0.67 Mn0.5 Fe0.5 O2 through a synergy of Li2 TiO3 coating and Li/Ti co‐doping. O 2− is oxidized to molecular O2 and peroxide (O2 ) n − ( n <2) during charging. Molecular O2 derived from transition metal (TM) migration is related to the superstructure ordering induced by Li doping. The synergy mechanism of Li2 TiO3 coating and Li/Ti co‐doping on the two O‐redox modes is revealed. Firstly, Li2 TiO3 coating restrains the surface O2 and inhibits O2 loss. Secondly, nonbonding Li−O−Na enhances the reversibility of O 2− →(O2 ) n − . Thirdly, Ti doping strengthens the TM−O bond which fixes lattice oxygen. The cationic redox reversibility is also enhanced by Li/Ti co‐doping. The proposed insights into the oxygen redox reversibility are insightful for other oxide cathodes. Abstract : How to improve the reversibility of O‐redox chemistry is particularly important for P2‐type layered cathodes in sodium‐ion batteries. Herein, the bulk O2 and nonbonding oxygen state for the reversible O‐redox in P2‐Na0.67 Mn0.5 Fe0.5 O2 has been successfully tuned through a synergy of Li2 TiO3 coating and Li/Ti co‐doping. The underlying mechanism has been revealed by neutron diffraction, resonant inelastic X‐ray scattering, density functional theory, etc.